Partnership Between Academic and Public Health to Train Public Health Nurses New Chronic Diseases Protocols - Kathryn Martin; Elena Wood; Stephen Goggans; Anthony Mulloy; Shilpa Brown; Paul Wallach (Georgia Southern University, 2017)
Background: According to the Georgia Department of Public Health (DPH), cardiovascular disease is the leading cause of death in Georgia (29% in 2013). Diabetes (DM) and hypertension (HTN) are known risk factors for cardiovascular disease. In 2013, the prevalence of diabetes was 11% and of hypertension was 35% of the state's adult population. There are not sufficient healthcare providers to manage these patients. To address this concern, the DPH Chronic Disease Prevention Section contracted with the Medical College of Georgia (MCG) at Augusta University to design and implement an innovative training program for Georgia public health nurses on diabetes and hypertension protocols. Methods: The two days' training consisted of lectures, workshops, case discussions, simulation, physical examination practice, and both written and clinical skills testing developed and presented by MCG faculty members in accordance with DPH DM and HTN protocols. The epidemiology, risk factors, disease process, and appropriate pharmacologic and non-pharmacologic management protocols were covered during the training sessions. Results: A post-training evaluation survey was conducted to evaluate accomplishment of the 10 learning objectives, the effectiveness of teaching approaches, appropriateness of training facilities, and whether personal learning goals were met. Participants rated "meeting program objectives" highly with 96% of responses "met", 3.5% "somewhat met", and 0.5% "not met". Participants were asked to rate personal knowledge of HTN and DM before and after the training (5-1 Likert scale with 5 = most knowledgeable and 1 = least knowledgeable). Average for pre-training was 3.0, and after the training 4.2. Conclusions: A partnership between the DPH and a public medical school resulted in a successful training of public health nurses. Participants agreed that the training effectively improved knowledge and ability to provide care with diabetic and hypertensive patients. Evaluation of the training on public health nurses' actual practice is desired, with the hope of disseminating better services to and improved healthcare for the population of Georgia. Key words: diabetes, hypertension, public health nurses, chronic diseases management, training